A STUDY OF AWARENESS ON E-RESOURCES AMONG B.ED STUDENT TEACHERS - J, Nithya; V.A, Malathi (International Journal of Research -GRANTHAALAYAH, 2017)
The essential of the study is the multiplying unfamiliarity of e-resources due to the let-down of electricity, which is a common problem in Palakkad area. Related other reasons are absence of time to utilize the I.T lab in time. The investigators and students from all disciplines are set to use e-Books in future. In order to build more teachers professional development and to improve the research practise they need in e-journals and e-books. The study aimed to examine the awareness on e-resources among B.Ed student teachers. The investigator adopted survey method to study the awareness on e-resources among B.Ed student teachers. For this study a sample of 200 B.Ed student teachers from three B.Ed training colleges which are situated in and around Palakkad district in Kerala selected by the investigator using simple random sampling technique. The findings reveal that there is no significant difference in the awareness of e-resources and e-resource technology among B.Ed Student Teachers.